Creating a Website-Based Company Profile Using Wordpress CMS at BUMN House Bandung - Deni Ramdhani (Ebiz Prima Nusa, 2024)
Rumah BUMN Bandung is the home for the development of MSMEs in all business actors in Bandung Raya. According to the current needs of every business actor and community, they have started to be literate with the needs of information technology. This project intends to produce website creation. The project design method is carried out with the help of the WordPress Content Management System (CMS) so that the Rumah BUMN Bandung website can be used as an information medium for company profiles. The stages of project implementation are also carried out in stages; starting from planning, design, development, testing, responsive web design (RWD) and deploying. The final stage, namely post-implementation, is carried out by reviewing the impact of the project through final interviews and distributing questionnaires. The results of reviewing the impact of the project through a questionnaire obtained the mean results for each variable; website quality, information quality, and interaction quality, are included in the very good criteria and are also supported by the results of website performance testing which are included in the optimal criteria.